Implementation of stunting prevention intervention policy in Penajam Paser Utara regency - Thalita Rifda Khaerani; Rafissah Adilah Khairunnisa (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Penajam Paser Utara Regency, one of the regencies in East Kalimantan, has implemented a stunting intervention program due to the high prevalence of stunting cases, which is currently at 24%. This research aims to investigate the implementation of stunting prevention intervention policy in Penajam Paser Utara Regency. The research design used is qualitative descriptive, employing data collection techniques such as observation, interviews, documentation, literature review, and analysis using an interactive model. The results of the study indicate that the intervention for stunting prevention in Penajam Paser Utara Regency involves several relevant government agencies (OPD) with roles corresponding to their respective tasks and functions. However, the implementation is primarily carried out through programs run by the Health Office, considering the program objectives, program funding/budget, program implementation timeline, and policy outputs. Abstrak: Kabupaten Penajam Paser utara salah satu kabupaten di Kalimantan Timur memiliki program intervensi stunting dikarenakan kasus stunting yang masih tergolong tinggi yaitu prevalensi sebanyak 24%. Penelitian ini bertujuan untuk mengetahui implementasi kebjakan intervensi pencegahan stunting di Kabupaten Penajam Paser Utara. Jenis penelitian yang digunakan deskriptif kualitatif dengan teknik kolesi data melalui observasi, wawancara, dokumentasi dan studi kepustakaan serta teknik analisis menggunakan model interaktif. Hasil penelititan menunjukan dalam mengintervensi pencegahan stunting di Kabupaten Penajam Paser Utara melibatkan beberapa OPD yang memiliki peran sesuai dengan tugas dan fungsi masing-masing namun dalam pelaksanaannya melalui program-program yang dijalankan oleh Dinas Kesehatan yang ditinjau dari tujuan, Pendanaan/Anggaran Program, Waktu Pelaksanaan Program dan Output Kebijakan